For documentary : twelve essays - Vaughan, Dai. (Berkeley : University of California Press, 1999)
These essays offer fresh and challenging insights into documentary. Vaughan makes his starting point plain: 'Most of us would feel that the word 'documentary' had not justified its place in the dictionary if the films so called did not manifest some relationship with the world not shared by others.' That elusive relationship is the subject of his eloquent reflections and analyses.
Let There Be Lumiere -- The Space between Shots -- Arms and the Absent -- The Aesthetics of Ambiguity -- What Do We Mean by "What"? -- Berlin versus Tokyo -- Notes on the Ascent of a Fictitious Mountain -- Rooting for Magoo -- Competing with Reality -- Salvatore Giuliano -- From Today, Cinema Is Dead -- A Light Not Its Own.
Includes index.
Print version record.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Documentary films -- History and criticism; Documentaires -- Histoire et critique; LANGUAGE ARTS & DISCIPLINES -- Journalism; Documentary films; Dokumentarfilm; Documentaires; Films documentaires -- Histoire et critique; Criticism, interpretation, etc